Awareness of Phonetic Considerations in the Construction of Removable Dental Prostheses Among Dental Students: A Cross-Sectional Survey - Sonal Jain; Karthiha Ramalingam; Kayathri Anbarasu; Arun Sarfoji; S. Vaibava Keerthana; K. Priyadharshini (Journal of Pharmacy and Bioallied Sciences)
Background: The role of phonetics in the construction of removable dental prostheses is critical for ensuring patient satisfaction and optimal functionality. This study aims to evaluate the awareness and understanding of phonetic considerations among dental students during the fabrication of removable prostheses. Materials and Methods: A questionnaire-based cross-sectional study was conducted among 150 dental students. The questionnaire comprised 20 items assessing students’ knowledge, attitudes, and practices regarding the role of phonetics in removable dental prostheses. Data were analyzed using descriptive statistics and Chi-square tests to determine the significance of differences among various groups. Results: Out of 150 respondents, 120 (80%) were aware of the importance of phonetics in the construction of removable dental prostheses. Among them, 95 (63.3%) had received formal training on this topic, while 25 (16.7%) had learned through clinical experience. The majority (85%) of students recognized the impact of phonetic issues on patient comfort and satisfaction. However, only 60% of students routinely incorporated phonetic assessments during prosthesis construction. The Chi-square test revealed a significant difference in awareness levels between students in different years of study (P < 0.05). Conclusion: This study highlights a moderate level of awareness among dental students regarding the role of phonetics in removable dental prostheses. While most students understand its importance, there is a gap in practical application, indicating a need for enhanced curriculum and training focused on phonetic considerations.